Depression and spousal violence in Peruvians pregnant during the COVID-19 pandemic - Medina-Quispe, Camila I. (2023)
Introduction: The restrictive measures chosen to reduce COVID-19 infection could maintain and even increase high levels of depression and violence, putting at risk both the fetus and the mother. Objective: To identify the prevalence and factors associated with depression in pregnant Peruvians during the COVID-19 pandemic. The study: Observational-analytical study, with 267 pregnant women in their third trimester of pregnancy. Conducted during the month of January 2021, applying the Edinburgh Scale and the Spanish version of the Index of Spouse Abuse-19 (ISA-19). Findings: 62.17% of pregnant women presented depression and 17.6% spousal violence during pregnancy. Spousal violence, the history of at least one lost pregnancy and planned pregnancy, were associated with depression. Conclusions: Spousal violence increases the prevalence of depression during pregnancy as opposed to a planned pregnancy or the history of at least one lost pregnancy.